Fluorescence, FT-IR and GC-MS determination of bioactive constituents of leaf extract of clitoria ternatea - R. KAVITHA (International Journal of Pharma and Bio Sciences, 2017)
Medicinal plants play a key role in human health care from ancient period. India is blessed with several herbal plants for the treatment of major and minor health problems without studying any phytochemical in detail. Plants are a rich source of bioactive constituents with interesting biological activities and are considered to be less toxic and free from side effects compared to synthetic drugs. Clitoria ternatea a valuable medicinal plant used in Ayurveda and Siddha medicine for the treatment of various diseases. The present study was to analyze the bioactive compounds from ethanolic extract of leaf of Clitoria ternatea L. by FT-IR and GC-MS techniques. The FT-IR analysis identified the functional groups such as primary alcohols, phenolics, alkane, alkynes and ketones. GC-MS revealed the presence of various bioactive compounds like -(2-ethylhexyl) phthalate, (2S,5S)-2,5-dimethyl-2-phenyl-1,3-dioxolane-4-one, 5,10-dihexyl-5,10-dihydroindolo (3,2-b) indole-2,7 dicarbaldehyde, 9,12-octadecadienoic acid (Z,Z), 2-hydroxy-1-(hydroxyl methyl) ethyl ester (CAS), neophytadiene and nonacosane (CAS). Phytochemical analysis showed the presence of various bioactive compounds which are known to exhibit medicinal activities.